2018
DOI: 10.1242/dmm.036012
|View full text |Cite
|
Sign up to set email alerts
|

Dietary advanced glycation end-product consumption leads to mechanical stiffening of murine intervertebral discs

Abstract: Back pain is a leading cause of disability and is strongly associated with intervertebral disc (IVD) degeneration. Reducing structural disruption and catabolism in IVD degeneration remains an important clinical challenge. Pro-oxidant and structure-modifying advanced glycation end-products (AGEs) contribute to obesity and diabetes, which are associated with increased back pain, and accumulate in tissues due to hyperglycemia or ingestion of foods processed at high heat. Collagen-rich IVDs are particularly suscep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 68 publications
(78 reference statements)
1
38
0
Order By: Relevance
“…An important finding of this study is that solute uptake in both treated and untreated CEPs was lowest in tissues with high AGE concentrations (Fig 4, S5 Fig). AGEs are formed through non-enzymatic glycation of the free amino groups of proteins by reducing sugars, and AGE accumulation in low-turnover proteins of the disc increases with ageing [41] and is accelerated by metabolic disease [4244] and with AGE-rich diets [45]. High AGE concentrations could negatively impact solute uptake in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…An important finding of this study is that solute uptake in both treated and untreated CEPs was lowest in tissues with high AGE concentrations (Fig 4, S5 Fig). AGEs are formed through non-enzymatic glycation of the free amino groups of proteins by reducing sugars, and AGE accumulation in low-turnover proteins of the disc increases with ageing [41] and is accelerated by metabolic disease [4244] and with AGE-rich diets [45]. High AGE concentrations could negatively impact solute uptake in several ways.…”
Section: Discussionmentioning
confidence: 99%
“…The specific structural changes to the IVD ECM due to AGE exposure in the presence of RAGE are not well‐understood and we believe this is partly due to limitations in the methods used to identify early degenerative changes to the ECM that mark the initiation of a degenerative cascade. Recently, we demonstrated that dietary accumulation of AGEs in the IVD increased levels of molecular level collagen degradation, 15 highlighting the direct contributions that AGEs can make to IVD degeneration. We believe that an improved understanding of the factors that cause early degenerative changes and the events that are subsequent to initiation of these changes may inform methods to detect and prevent such contributors to IVD degeneration.…”
Section: Introductionmentioning
confidence: 94%
“…There is mounting evidence for a causal relationship between IVD degeneration and AGEs. AGEs can accumulate in spinal tissues from aging, high‐AGE (H‐AGE) diets (eg, highly processed western diets) and diabetes, and are associated with structural changes in the IVD including decreased glycosaminoglycan content, 13‐15 increased vertebral bone changes, 16 and increased collagen degradation 15 . In addition, the receptor for AGEs (RAGE) has been observed to initiate an NF‐kB mediated inflammatory response in both human and mice IVD tissue exposed to AGEs 17,18 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testing protocol was adopted from our previous studies [43][44][45]. In brief, on the day of testing, after 10 mins in PBS for thawing and hydrating, the motion segment specimens were loaded into parallel-platens of an axial loading machine (Bose ElectroForce 3220; TA Instruments, New Castle, DE, USA) using a custom-designed fixture with a fluid bath of PBS for axial testing.…”
Section: Motion Segment Biomechanicsmentioning
confidence: 99%